Fine-tuning banana Xanthomonas wilt control options over the past decade in East and Central Africa - Blomme, Guy; Jacobsen, K.; Ocimati, W.; Ntamwira, J.; Sivirihauma, Charles; Ssekiwoko, F.; Beed, Fenton D.; Nakato, V.; Kubiriba, Jerome; Tripathi, L.; Mbolela, F.; Lutete, L.; et al. (Springer, 2014)
Xanthomonas wilt, caused by Xanthomonas campestris pv. musacearum has, since 2001, become the most important and widespread disease of Musa in East and Central Africa. Over the past decade, new research findings and especially feedback from small-scale farmers have helped in fine-tuning Xanthomonas wilt control options. During the initial years of the Xanthomonas wilt epidemic in East Africa, the complete uprooting of diseased mats and the burning or burying of plant debris was advocated as part of a control package which included the use of clean garden tools and early removal of male buds to prevent insect vector transmission. Uprooting a complete mat (i.e. the mother plant and a varying number of lateral shoots) is understandably time-consuming and labour intensive and becomes very cumbersome when a large number of diseased mats have to be removed. Recent research findings suggest that Xcm bacteria do not colonize all lateral shoots (i.e. incomplete systemicity occurs) and even when present that this does not necessarily lead to symptom expression and disease. This led to a new control method whereby only the visibly diseased plants within a mat are cut at soil level. The underlying idea is that the continued removal of only the diseased plants in a field will reduce the inoculum level and will bring down disease incidence to an acceptable level. This method is less labour intensive and takes a short time compared to the removal of a complete mat. However, single diseased stem removal needs to go hand in hand with prevention of new infections that can occur through the use of contaminated garden tools or through insect vector transmission. Novel transgenic approaches are also discussed. This paper presents an overview of past and ongoing research towards the development of a more practical and less demanding control strategy for Xanthomonas wilt.